Plasma interferon predicts pulmonary hypertension severity and outcome - Liang, Zhanping; Li, Yun; Jia, Shuying; Liu, Yuyan; Zhu, Jie; Li, Jinling; Li, Fei; Xia, Xiaohuan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPulmonary hypertension (PH) is a complex and progressive disease characterized by elevated pulmonary vascular resistance. Inflammation plays an important role in the pathogenesis of PH. Interferons (IFNs) are key immune cytokines that regulate cellular responses to various stimuli. This study aimed to investigate the association between IFN levels and the risk and prognosis of PH.MethodsA cohort of 875 PH patients and 182 matched controls were included in this study. Logistic regression models and receiver operating characteristic (ROC) curves were applied to evaluate the association between IFN levels and PH risk. Correlations between variables were assessed using Spearman's rank correlation coefficient (r ). Cox proportional hazards regression and Kaplan-Meier survival curves were used to assess the prognostic value of IFNs levels. The predictive performance of prognostic models was assessed using ROC analysis and decision curve analysis and a nomogram was constructed to estimate individual overall survival probabilities.ResultsBoth IFN-α and IFN-γ levels were significantly elevated in PH patients compared with controls (P < 0.05 for both), with IFN-α showing stronger predictive value across multiple PH subgroups (P < 0.05 for all), particularly in patients with Group 4 PH and idiopathic pulmonary arterial hypertension (IPAH). In Cox regression models, IFN-α was significantly associated with lower survival in PH patients (HR: 1.120, 95% CI: 1.001-1.253, P = 0.048). Kaplan-Meier analysis demonstrated that patients with IFN-α > 2.131 pg/mL had significantly lower 5-year cumulative survival rate of 60.1%, compared with 81.2% for those with IFN-α ≤ 2.131 pg/mL (Log Rank P < 0.001). A prognostic model combining IFN-α with traditional clinical markers, such as WHO-FC, 6-MWD, and NT-proBNP, improved predictive accuracy, with IFN-α contributing additional clinical net benefit in risk stratification.ConclusionsThese findings suggest that plasma IFN-α may serve as a valuable biomarker for both predicting PH risk and assessing prognosis.